(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
The coastal region of Bangladesh is highly vulnerable to the adverse effects of tropical cyclones, and the changing climate has exacerbated the impacts of these cyclones and the subsequent storm surges. Moreover, characteristics of the coastal region can amplify the impact of tropical cyclones. Over the years, many cyclones have made landfall in Bangladesh’s western and central coastal regions. Recently, two cyclones that have impacted the western and central coastal regions are Bulbul in 2019 and Sitrang in 2022. To evaluate the impact of these cyclones, the Delft3d modeling suite has been used. The model was validated by comparing the simulated data with tidal records collected from BIWTA, demonstrating its ability to replicate real-life scenarios accurately. For cyclone Bulbul, the coefficient of determination, RMSE, and MAE were 0.69, 0.34, and 0.24, respectively. For cyclone Sitrang, these values were 0.838, 0.32, and 0.28 for Hiron Point and 0.84, 0.53, and 0.4 for Chattogram. The inundation area for tropical cyclone Bulbul was 2255 square kilometers, while cyclone Sitrang resulted in the flooding of 1908 square kilometers. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(1), 2025, P 65-75